2004
DOI: 10.1086/502317
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Rates of Inpatient Pneumococcal Vaccination: Impact of Standing Orders Versus Computerized Reminders to Physicians

Abstract: Although both interventions were effective in increasing inpatient pneumococcal vaccination rates relative to baseline practice, physician independent initiation of standing orders was clearly more effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…43 Outcomes All studies reported data on the primary outcome. In inpatient and primary care settings, vaccination rates among eligible patients in the included studies ranged from 42% to 73% with standing orders 32,37 and from 15% to 59.7% with physician reminders, 32,37,39,43 these percentages being much higher compared to rates in control groups who received no intervention, providing evidence that both standing orders protocols and computerized reminders to physicians are effective strategies to increase vaccination rates. 37,39 In emergency department settings computerized reminder system increased vaccination rate from a baseline of 38.8% to 45.4%.…”
Section: New Media Applied To Provider-based Interventions Computerizmentioning
confidence: 91%
See 2 more Smart Citations
“…43 Outcomes All studies reported data on the primary outcome. In inpatient and primary care settings, vaccination rates among eligible patients in the included studies ranged from 42% to 73% with standing orders 32,37 and from 15% to 59.7% with physician reminders, 32,37,39,43 these percentages being much higher compared to rates in control groups who received no intervention, providing evidence that both standing orders protocols and computerized reminders to physicians are effective strategies to increase vaccination rates. 37,39 In emergency department settings computerized reminder system increased vaccination rate from a baseline of 38.8% to 45.4%.…”
Section: New Media Applied To Provider-based Interventions Computerizmentioning
confidence: 91%
“…In particular, we considered seven randomized controlled trials, 26,[31][32][33][34][35][36] five non-randomized trials, 27,30,37-39 three cross-sectional studies, 29,40,41 one case-control study, 42 and three studies that we considered to have an operational research approach. 37,43,44 Studies' sample size ranged from 50 to 9213 subjects (median = 341). One paper described two different studies.…”
Section: Identified Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This idea has been trialed with inhospital vaccination against infl uenza and Streptococcus pneumonia. 27 Our initial strategy did not include opt-out www.hospitalpediatrics.org ordering for vitamin D because our current EMR was unable to correctly identify breastfed infants. Additionally, although an opt-out order may have achieved higher vitamin D prescribing rates, the fact that most infants (63.2%, 810/1281) in our sample did not meet criteria for vitamin D supplementation made opt-in ordering a more suitable initial approach.…”
Section: Discussionmentioning
confidence: 99%
“…Dexter et al [40] found the vaccination rate for standing orders (51%) significantly higher when compared with the rate for computer generated physician reminders (31%). Coyle et al [41] also found the standing order rate (98%) to be significantly higher than the computerized physician reminder rate (23%) suggesting the need for further research to identify the circumstances where each intervention or combination of interventions is most effective. While the implementation of standing orders is, relatively speaking, a straightforward intervention, the implementation of a clinical reminder system is more complex and its successful implementation/use are more affected by nuances of the specific implementation [42][43][44].…”
Section: The Experience Of the Veterans Healthcare Administrationmentioning
confidence: 99%